2017
DOI: 10.1093/ageing/afw244
|View full text |Cite
|
Sign up to set email alerts
|

The competencies of Registered Nurses working in care homes: a modified Delphi study

Abstract: BACKGROUND: Registered Nurses (RNs) working in UK care homes receive most of their training in acute hospitals. At present the role of care home nursing is underdeveloped and it is seen as a low status career. We describe here research to define core competencies for RNs working in UK care homes. METHODS:A two-stage process was adopted. A systematic literature review and focus groups with stakeholders provided an initial list of competencies. The competency list was modified over three rounds of a Delphi proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…Recruiting and retaining nurses is challenging, and it is disquieting that nurses leave their jobs in the municipalities (Cooper et al, 2017). It is likely that there is a relationship between high turnover rates and nurses' perceptions of low competency in long-term care (Stanyon, Goldberg, Astle, Griffiths, & Gordon, 2017). However, leadership focusing on task completion alone is not sufficient to achieve optimum outcomes for the nursing workforce (Cummings et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recruiting and retaining nurses is challenging, and it is disquieting that nurses leave their jobs in the municipalities (Cooper et al, 2017). It is likely that there is a relationship between high turnover rates and nurses' perceptions of low competency in long-term care (Stanyon, Goldberg, Astle, Griffiths, & Gordon, 2017). However, leadership focusing on task completion alone is not sufficient to achieve optimum outcomes for the nursing workforce (Cummings et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In LTC settings, where physicians are relatively absent, nurses are the key healthcare professionals. EOL care is an important competency for nurses in LTC settings (Stanyon, Goldberg, Astle, Griffiths, & Gordon, 2017). Studies have shown that nurses in LTC settings seek to alleviate suffering (Dwyer, Hansebo, Andershed, & Ternestedt, 2010), include family members and physicians in planning for the future (Gorlén, Gorlén, & Neergaard, 2013;Koppitz, Bosshard, Kipfer, & Imhof, 2016), play advocator and mediator roles in EOL-care decision-making (Kobayashi & Yamashita, 2016;Lopez, 2009;Phillips et al, 2006), find meaning in residents' everyday lives (Dwyer et al, 2010), and support relatives to help residents die with dignity (Hov, Hedelin, & Athlin, 2013;Kaasalainen, Brazil, Ploeg, & Martin, 2007;Sakashita & Nishida, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, healthcare professionals globally of all hues have neglected research, recruitment incentivization and quality improvement in nursing home care relative to other areas of clinical practice 4 . This is further reflected by evidence of variable and often inadequate preparation for pandemics in the sector 5,6 , as well as the absence of infection control from descriptions of the competencies of nurses in care homes 7 .…”
mentioning
confidence: 99%